Effect of practice hours on elite junior tennis players` burnout: Gender differences - Mouelhi-Guizani, S.; Guinoubi, S.; Teyeb, N.; Chtara, M.; Crespo, M. (International Journal of Sports Science & Coaching, 2022)
This study investigated the effect of training hours on elite junior tennis players` burnout with attention to gender differences. A quantitative cross-sectional design was used in this research. A sample of 70 junior elite Tunisian tennis players (17.01 ± 0.81y) completed a demographic and the Athlete Burnout Questionnaire. Results showed that 64% (n = 45) had a low risk, 14% (n = 10) had a moderate risk, 13% (n = 9) showed a high risk of burnout and 9% (n = 6) had burnout with individual differences. Analysis of variance revealed that players who trained more than 12 h (high volume) reported significantly higher scores of the burnout dimensions: emotional and physical exhaustion (p < 0.001; d = 2.18); sport devaluation (p < 0.001; d = 2.36); reduced sense of accomplishment (p < 0.001; d = 2.27); as well general burnout (p < 0.01; d = 2.69), than players that trained less than 12 h (moderate volume and low volume). The effect of gender was observed in the variables of emotional and physical exhaustion (t = 2.17; p < 0.03), sport devaluation (t = 2.23; p < 0.029), reduced sense of accomplishment (t = 2.58; p < 0.012) and general burnout (t = 2.41; p < 0.019) with female players showing higher scores in all of the burnout dimensions. It was concluded that the high volume of weekly training hours by junior players was associated with higher levels of the general burnout scores and that female players showed higher burnout scores than their male counterparts.